Re-refining Used Engine Oil in Ghana Using Solvent Extraction and Acid-Clay Treatment - Emmanuela Kwao-Boateng; Terza Anokye-Poku; Anthony N. P. Agyemang; Michael Kwadwo Fokuo (International Journal of Chemical Engineering)
Despite having detrimental impacts on the environment and human health, used engine oil is not properly disposed of in Ghana. However, used engine oil can be a valuable resource when recycled. This study investigates the recovery of base oils from used engine oils collected in one Ghanaian municipality. The used engine oils are re-refined either through acid-clay treatment or solvent extraction. Pour point, density, viscosity index, and total acid number of used engine oil and re-refined oils were measured in order to evaluate the two re-refining processes used and assess whether it is appropriate to reuse the re-refined oils as base oils. The pour point, total acid number, and viscosity index of the re-refined oils were significantly different from those of the used engine oils. The density of the re-refined oils varied little from that of the used engine oils (by 0.83% to 6.65%). These changes indicate the separation of some components, primarily impurities, from used engine oil as a result of re-refining. Compared to solvent extraction, acid-clay treatment was found to be less selective. When nitric acid or sulphuric acid was used, acid-clay treatment often produced group I and II base oils, whereas hydrochloric acid typically produced group III base oils. Also, the solvent extraction process frequently yielded oils with very high viscosity indices comparable to group III base oils. It is recommended that the type of base oil preferred for the production of new lubricants should be taken into account when deciding on a specific method for re-refining used engine oil.